2005
DOI: 10.1007/s11230-004-6343-9
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of the species of Myxobolus Bütschli, 1882 (Myxozoa: Myxosporea: Myxobolidae)

Abstract: A synopsis of 744 nominal species of Myxobolus Bu¨tschli, 1882 (Myxozoa, Myxosporea, Myxobolidae) is presented. For each species, the relevant morphometric and morphological data are indicated, as well as the host(s), site(s) of infection within the host and type-locality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
189
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(203 citation statements)
references
References 105 publications
4
189
0
10
Order By: Relevance
“…Comparison of our results with other Myxobolus species that infect the gills of Brazilian freshwater fish (Table) revealed significant differences in morphometric characters (size and body shape) of the spores, ultrastructural organisation of the PCs and their PFCs and host specificity. However, when comparing other international Myxobolus species that infect the gill tissues of freshwater fish (Eiras et al 2005b) to those described herein, we observed that spores with a similar shape and size have several morphological differences in both length and width of PC as well as their position in relation to the PC axis. This analysis suggests that the presently described parasite is different from other Myxobolus spp and therefore, M. sciades is a new species.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Comparison of our results with other Myxobolus species that infect the gills of Brazilian freshwater fish (Table) revealed significant differences in morphometric characters (size and body shape) of the spores, ultrastructural organisation of the PCs and their PFCs and host specificity. However, when comparing other international Myxobolus species that infect the gill tissues of freshwater fish (Eiras et al 2005b) to those described herein, we observed that spores with a similar shape and size have several morphological differences in both length and width of PC as well as their position in relation to the PC axis. This analysis suggests that the presently described parasite is different from other Myxobolus spp and therefore, M. sciades is a new species.…”
Section: Discussionmentioning
confidence: 54%
“…The spores were pyriform and uninucleate, measuring 9.15 ± 0.39 μm (n = 50) long, 4.36 ± 0.23 μm (n = 25) wide and 2.61 ± 0.31 μm (n = 25) The genus Myxobolus (Bütschli, 1882) (family Myxobolidae) is one of the largest myxosporean groups and its members are important pathogens of freshwater and marine fish in several geographical areas (Eiras et al 2005b, Lom & Dyková 2006. In a recent synopsis, 744 Myxobolus species have been identified parasitizing fish (Eiras et al 2005b) and more recently, 792 named species of the same genus, including seven infecting amphibians, have been described (Lom & Dyková 2006). However, this number has been successively increasing over the years by the continuing description of new species in different countries, including Brazil (Casal et al 2006, Martins & Onaka 2006, Eiras et al 2007, Adriano et al 2009a, b, Azevedo et al 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Myxobolus is the richest group among myxosporea, containing about 744 nominal species (Eiras et al 2005), among which 328 species were reported in China (Chen and Ma 1998). Most of these species, however, were described a long time ago with poor data and illustrations available (Ward 1919;Tripathi 1952;Fomena and Bouix 1997).…”
Section: Discussionmentioning
confidence: 99%